Delaying the Age of Marriage From the Perspective of Contemporary Fiqh and Maqāṣid Al-Sharīʿah - Mahfuz Assiddiq; Nadia Khaerunnisa; M. Tahir Maloko; Achmad Musyahid (Al-Fikru: Jurnal Ilmiah, 2025)
The trend of delaying marriage in contemporary Muslim societies has increased in line with social, economic, and cultural changes. This phenomenon has sparked normative debates in Islamic law as it conflicts with the recommendation to marry early and raises concerns about moral and social impacts. This study aims to analyze the social and moral implications of delaying marriage age through the perspective of contemporary fiqh using the maqāṣid al-syarī‘ah approach. The research uses a qualitative method with a literature review, with data sources in the form of classical and contemporary fiqh literature, works on maqāṣid al-syarī‘ah, as well as secondary data from official reports from the Central Statistics Agency and BKKBN and relevant scientific articles. The analysis was conducted descriptively and analytically by considering the practice of postponing marriage based on the principle of jalb al-maṣāliḥ wa dar’ al-mafāsid. The results of the study show that postponing marriage can be beneficial if it serves to mature economic, psychological, and social readiness, but has the potential to become harmful if it opens up space for moral violations and weakens self-control. A reinterpretation of the concept of istiṭā‘ah based on maqāṣid is necessary so that legal assessments are contextual and proportional.